Access to Public Information in the Form of Documents of the Supreme Audit Office Audit Proceedings (Ius Novum, 2025)
Access to public information, regulated in Article 61 of the Constitution of the Republic of Poland and the Act of 6 September 2001, is an element of public scrutiny of public authorities that enables the public to supervise public entities on a regular basis. The Supreme Audit Office [NIK], as the chief organ of state audit, is obliged to provide public information. The application of the Act on Access to Public Information to NIK’s audit results raises doubts, particularly in the context of other acts specifying different rules of access to information. Article 10 of the Act on the Supreme Audit Office establishes the obligation of the President of NIK to disclose certain documents; however, this does not preclude the application of the Act on Access to Public Information to other documents after the conclusion of audit proceedings. Audit programmes and subject matters are protected by audit confidentiality, but they may be disclosed once the audit has been completed, provided they are not deemed internal documents. These documents are crucial for assessing the integrity of NIK’s activities. Although audit proceeding files may not be considered public information as a whole, individual documents contained within the files constitute public information.
Keywords: Supreme Audit Office, Supreme Chamber of Control, public information, internal document, audit files